An Analytical Study of Female Characters in Twentieth Century Urdu Novels - Dr. Aasma Rani; Dr Aqsa Naseem Sandhu (Zaban-o-Adab, 2025)
The analysis of feminine character in Urdu novels explores the evolution, representation, and socio-cultural implications of female protagonists and supporting characters. This study examines how women are portrayed across different periods of Urdu literature, reflecting societal changes, gender roles, and feminist discourse. It delves into the psychological depth, struggles, and aspirations of female characters, assessing their roles as traditional caregivers, rebels, or empowered individuals challenging patriarchy. The research highlights the influence of historical, political, and literary movements on the construction of feminine identity in Urdu fiction. By analyzing works of renowned novelists, the study provides insights into the dynamic interplay between literature and women’s status in society.